2014
DOI: 10.1007/s10522-014-9505-4
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of cytochemical and fluorescence methods of senescence-associated β-galactosidase detection for ageing driven by replication and time

Abstract: Senescence-associated β-galactosidase (SA-β-Gal) is a widely used marker of senescent cells in vitro and in vivo. In this report, young and senescent human peritoneal mesothelial cells (HPMCs) and fragments of the omentum, from which these cells were isolated, were subjected to simultaneous examination of SA-β-Gal using two methods, i.e. cytochemical and fluorescent methods. The results obtained were confronted with the cumulative number of population doublings (CPD) and the calendar age of the tissue donor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…The presence of mesothelial cells, staying in agreement with the results of Steinkamp et al [23], may imply that their involvement in peritoneal ovarian cancer metastasis not only encompasses the very early steps of cancer cell dissemination (until their "clearance" [3,15]), but may also last continuously, probably amplifying their harmful activity (pro-adhesive [6], pro-angiogenic [24], EMT-promoting [25]) when they approach senescence. This sequence of events could explain the age-dependent increase in the intraperitoneal aggressiveness of ovarian cancer [26], especially when taking into account the fact that senescent HPMCs accumulate in the omental tissue during aging in vivo [27]. It is also worth noting that the adhesionand growth-promoting activities of HPMCs toward ovarian malignancy in vitro as well as their positive effect on xenograft development in vivo were consistent and not related to the health status and surgery reason of the donor from whom the HPMCs were established.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of mesothelial cells, staying in agreement with the results of Steinkamp et al [23], may imply that their involvement in peritoneal ovarian cancer metastasis not only encompasses the very early steps of cancer cell dissemination (until their "clearance" [3,15]), but may also last continuously, probably amplifying their harmful activity (pro-adhesive [6], pro-angiogenic [24], EMT-promoting [25]) when they approach senescence. This sequence of events could explain the age-dependent increase in the intraperitoneal aggressiveness of ovarian cancer [26], especially when taking into account the fact that senescent HPMCs accumulate in the omental tissue during aging in vivo [27]. It is also worth noting that the adhesionand growth-promoting activities of HPMCs toward ovarian malignancy in vitro as well as their positive effect on xenograft development in vivo were consistent and not related to the health status and surgery reason of the donor from whom the HPMCs were established.…”
Section: Resultsmentioning
confidence: 99%
“…In this context it should be stressed that HPMCs with biochemical features of senescence accumulate progressively in the peritoneum during aging also in non-cancerous patients. 25 This may indicate that they create in the peritoneal cavity a niche in which cancer cells encounter hospitable conditions allowing them to efficiently disseminate. This scenario seems to be of special importance in face of findings by Krtolica et al , 15 who demonstrated that senescent cells can exert their pro-cancerous activity even when their fraction is as small as 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is not only an in vitro phenomenon, or an artifact of cell culture, as was postulated by some authors [69]. The presence of senescent cells has been documented in various tissues, including in the skin [22], kidney [70], blood vessels [71], prostate [72], and peritoneal cavity [73], implying that they may play some role in these tissues in physiology and/or pathology. Answering the question about the role of senescent cells accumulating in vivo is far more difficult.…”
Section: Biological Rolementioning
confidence: 87%